Gambaran Tingkat Kontrol Asma pada Pasien Asma di Poli Paru Rumah Sakit Umum Daerah Bendan Kota Pekalongan - Edwin Donny Yahya; Dian Kartikasari (Universitas Malahayati, 2023)
ABSTRACT Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation. Asthma is defined by a history of respiratory symptoms such as wheezing, shortness of breath, chest tightness, and cough that vary over time. The more frequent asthma attacks occur, the more fatal and will inevitably affect daily activities, such as school attendance, work, and other physical activities. Asthma is difficult to cure but can be controlled using the Asthma Control Test (ACT) questionnaire to determine the level of asthma control and maintain asthma in a well-controlled condition so that it does not affect daily activities. This study aims to determine the level of asthma control in asthmatic patients at the Pulmonary Polyclinic, Bendan Regional General Hospital, Pekalongan City. This research is a quantitative research with a descriptive research design, survey approach. For data collection using total sampling technique. The results of this study found that the description of the level of asthma control in asthma patients at the Pulmonary Polyclinic of Bendan Regional General Hospital Pekalongan City was largely uncontrolled. In this study, the results obtained were controlled 5 (11.4%), partially controlled 10 (22.7%), uncontrolled 29 (65.9%). The results of this study indicate that the level of asthma control in acid patients at the Pulmonary Polyclinic of Bendan Regional General Hospital, Pekalongan City is not controlled. Keywords : Asthma Patients, Level Of Asthma Control ABSTRAK Asma merupakan suatu penyakit heterogen, biasanya ditandai dengan peradangan saluran napas kronis. Asma didefinisikan oleh riwayat gejala pernafasan seperti mengi, sesak nafas, sesak dada, dan batuk yang bervariasi dari waktu ke waktu. Semakin sering serangan asma terjadi semakin fatal dan pasti akan mempengaruhi aktivitas sehari-hari, seperti kehadiran sekolah, pekerjaan, dan aktivitas fisik lainya. Asma sulit disembuhkan tetapi dapat dikontrol menggunakan kuesioner Asthma Control Test (ACT) untuk mengetahui tingkat kontrol asma dan mempertahankan asma dengan kondisi terkontrol dengan baik agar tidak mempengaruhi aktivitas sehari-hari. Penelitian ini bertujuan untuk mengetahui tingkat kontrol asma pada pasien asma di Poli Paru Rumah Sakit Umum Daerah Bendan Kota Pekalongan. Penelitian ini adalah penelitian kuantitatif dengan desain penelitian deskriptif, pendekatan Survey. Untuk pengumpulan data menggunakan teknik total sampling. Hasil penelitian ini didapatkan bahwa gambaran tingkat kontrol asma pada pasien asma di Poli Paru Rumah Sakit Umum Daerah Bendan Kota Pekalongan sebagian besar tidak terkontrol. Dalam penelitian ini diperoleh hasil sebanyak terkontrol 5 (11,4%), terkontrol sebagian 10 (22,7%), tidak terkontrol 29 (65,9%). Hasil penelitian ini menunjukan bahwa tingkat kontrol asma pada pasien asam di Poli Paru Rumah Sakit Umum Daerah Bendan Kota Pekalongan adalah tidak terkontrol. Kata Kunci: Pasien Asma, Tingkat Kontrol Asma